THE IMPLEMENTATION OF HIJRAH IN THE SAHABAT HIJRAH MAKASSAR (LIVING SUNNAH STUDY) - Basir, Zulkifli; Darussalam, Andi; Mahmuddin, Mahmuddin (Program Pascasarjana, UIN Alauddin Makassar, 2020)
This research is aimed to discover the meaning of the hijrah hadith; and the implementation of hijrah in the Sahabat Hijrah Makassar Community (the fellow hijrah community Makassar). This is a field-reference research in which the data is obtained from takhrij hadith, observations and interviews. The researcher then reviews and concludes the result. The hadith used in this research are sahih (valid) and contain versatile contents such as the intentions of hijrah, religious practices equals to hijrah, and the the fail of hijrah. The meaning of hijrah according to the Sahabat Hijrah Makassar Community is divided into two aspects. Those are the understanding of hijrah hadith and the understanding of hijrah out of the hadith context, for example, repentance and identity. The living sunnah is a brand new kind of research that is openly acceptable to the hadith research. The absence of model and analysis for this method is expected to florish the living sunnah studies and discourses in Indonesia. The hijrah movement in Indonesia begins with dakwah by the millennials. Therefore, the government is expected to be aware of this communities.